HUBUNGAN KONFLIK DENGAN KINERJA PEGAWAI BIRO BINA SOsSIAL SEKRETARIAT DAERAH PROVINSI SUMATERA BARAT - Mella Aldionita D (Universitas Negeri Padang, 2014)
The goal of this research are to see information about the Conflict Relationship with Employee Performance. The population is 65 employee and the sample is 56 people that taken by simple random sampling research. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the Conflict Relationship with Employee Performance in office Biro Bina Sosial Sekretariat Daerah Provinsi Sumatera Barat. Key word : Conflict and Employee Performance